Investigating Student Teachers’ Reflections on Early Field Experiences - Kanyarat Cojorn,; Kanyarat Sonsupap, (Journal of Educational Issues, 2024)
The purposes of the research were to (1) study the quality of reflections among student teachers in the categories of self-reflection and peer feedback and (2) compare the level of reflection between groups of teachers with less and more teaching experience. The sample consisted of 112 general science student teachers. An analytical framework of reflection quality in this study contained the topic of reflection and depth of reflection. The topic of reflection focused on five dimensions including: 1) teaching and learning strategies, 2) teacher’s appearance, 3) student’s experience, 4) learning achievement, and 5) pedagogical practice. The depth of reflection was categorized into 4 levels involving level one: description, level two: explanation, level three: insightful comment, and level four: recognized good practice. Data was collected from the reflection journals of the student teachers’ early field teaching experiences then analyzed by scoring reflective journals. The results indicated that the overall reflections were in level three: ‘Insightful Comment’ in both categories. In terms of student’s experience, and learning achievement were in level two ‘Explanation’. In comparison to student teachers’ reflections among the experience related to learning design, there was no significant difference between overall self-reflection and peer feedback. Some aspects were statistically significant, i.e., the student’s experience, and learning achievement between the group of less and more experience in learning design respectively. The findings showed the impact of experience on the reflections in student teachers. The study highlighted the implications of reflective practice for teacher education programs, science teacher education and research.